Efficacy and safety of an Ayurvedic Menohelp syrup in the management of heavy menstrual bleeding (menorrhagia): an open-label clinical study - Kamini Dhiman; Pradeep Kumar Prajapati; Deepika Gopal; Ashutosh Gautam; Rajat Singal (Drugs in Context, 2026)
Background: Heavy menstrual bleeding (HMB) is a common gynaecological condition that significantly affects the quality of life and daily functioning amongst women of reproductive age. In Ayurveda, this condition is described under the category of Asrigdara. Menohelp Syrup, an Ashoka (Saraca asoca)-based Ayurvedic formulation, is traditionally used for the management of HMB. This open-label study evaluated the efficacy and safety of Menohelp Syrup in women with HMB. The study aimed to assess reductions in menstrual blood loss and associated symptoms along with improvement in quality of life. Methods: This open-label clinical study included 228 non-pregnant women with HMB aged 18–45 years. Participants received Menohelp Syrup at a dose of 15 mL twice daily for 90 days. The primary outcome was menstrual blood loss assessed using the Pictorial Blood Assessment Chart. Secondary outcomes included bleeding duration, cycle regularity, pain-related symptoms, haemoglobin and haematological parameters, endometrial thickness, and quality of life assessed using the Menorrhagia Impact Questionnaire. Results: Treatment with Menohelp Syrup resulted in a substantial reduction in menstrual blood loss, with a 54% decrease in estimated menstrual blood loss and a 58% reduction in Pictorial Blood Assessment Chart scores from baseline to day 90. Improvement was also observed in bleeding duration, absorbent product usage, clot passage and bleeding-related urgency. Menstrual pain symptoms improved considerably, with 68.06% of participants reporting complete resolution of dysmenorrhoea at the end of treatment. Mean haemoglobin levels showed modest improvement, whilst endometrial thickness remained stable throughout the study period. No clinically significant adverse events were reported, indicating a favourable safety profile. Conclusions: Menohelp Syrup was well tolerated and was associated with clinically meaningful improvement in HMB, bleeding-related symptom burden and qualityof- life outcomes in women with HMB. These findings support the potential role of Menohelp Syrup as a safe, non-invasive therapeutic option for the management of HMB. Download the Plain Language Summary of this article: https://www.drugsincontext.com/plain-language-summaries/plain-language-summary-efficacy-and-safety-of-an-ayurvedic-menohelp-syrup-in-the-management-of-heavy-menstrual-bleeding-menorrhagia-an-open-label-clinical-study